Analysis of the Utilization of the Medan Berkah Health Insurance Program (JKMB) in the Belawan Sicanang Community - Pratiwi, Khairani Putri; Priyatna, Sekar Harum; Mawaddah, Qisti; Gurning, Fitriani Pramita (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
The Mayor of Medan refers to Universal Health Coverage as the Medan Berkah Health Insurance (JKMB) Program, which will be implemented in November 2022. The JKMB program is expected to free the general public from financial barriers to accessing adequate and high-quality healthcare. The purpose of this study is to examine how the Belawan Sicanang community uses and benefits from the Medan Berkah Health Insurance (JKMB) program. This study used a quantitative descriptive research design, with data collection based on questionnaires. Based on the research findings, which indicate that 75% of respondents in the Belawan Sicanang population are aware of the Medan Berkah Health Insurance program, respondents obtained information through social media, enabling them to effectively utilize the JKMB program.